Design and fabrication of a novel wideband tem – cell for dielectric measurements - Yahya Sayegh, Ahmed Mohammed (2011)
Dielectric properties measurement at microwave frequencies is required to illustrate how the electromagnetic waves propagate through the materials. Various methods have been used for the measurement of dielectric properties including both time and frequency domain methods. The existing systems are mainly based on coaxial probes, free space, and reflection/transmission method by using waveguide or coaxial cell and resonance techniques. Waveguide has the advantages of high power handling capability and low loss but it requires the sample to be machined out as fit as the cross section of the waveguide. Practically waveguides are not appropriate for lower frequencies due to the large size. Coaxial line technique has enough bandwidth but not easy to perform dielectric measurement for heavy and porous materials as concrete. It does not provide a uniform electromagnetic (EM) wave and the specimen needs to be in the shape of toroidal which is hard to achieve. In free space method a perfect normal plane wave is hard to achieve and as well as the diffraction effect of the sample edges cannot be avoided. In this project a novel wideband TEM cell in the frequency range from 50 MHz to 800 MHz based on parallel plate waveguide is presented suitable for transmission/reflection method. A specimen of dielectric material is put between the two parallel plates. The scattering parameters (S-parameters) of the two port line are measured using vector network analyzer. The Complex permittivity and permeability can be determined from the measured S-parameters using Nicolson-Ross-Weir (NRW) method. In order to validate the functionality of the parallel plate cell, the dielectric properties of Teflon is determined and shown. A good agreement among the experimental result, simulation result and the published values of the Teflon material is achieved. In addition to that the dielectric properties of concrete, wet and dry wood are investigated as well. Based on this agreement an original result of the dielectric properties of the concrete material is obtained and shown.